The Effectiveness of Tahsin Program and The Ability to Read Al Qur’an - arif, arif cahyono (Journal of Social Science, 2024)
This study describes the effectiveness of the Ummi Method Tahsin Program in an effort to improve the competence of reading the Qur'an for TPQ teachers. This research model is qualitative research using descriptive methods (library research). The data analysis process is carried out by means of: data reduction, data presentation and data verification. The results of the research are as follows; Effect or impact of the Ummi Method Tahsin Program implemented by the Taman Region Ummi Management in an effort to improve the competence of reading Al-qur'an prospective teachers or TPQ teachers according to the quality standards of the Ummi Method is getting better. The indicator is the increasing quality of Al-Qur'an Teachers and students in TPQ or in Islamic schools so that it has an impact on increasing the quantity of students who are included in the munaqasyah (Final Al-Qur'an Exam) organized by the Sidoarjo Regional Ummi Board 2 times a year